Is there a role for an external beam boost in cervical cancer radiotherapy?† - Sethi, Rajni A.; Jozsef, Gabor; Grew, David; Marciscano, Ariel; Pennell, Ryan; Babcock, Melissa; McCarthy, Allison; Curtin, John; Schiff, Peter B. (Frontiers in Oncology, 2013)
Abstract Objectives: Some patients are medically unfit for or averse to undergoing a brachytherapy boost as part of cervical cancer radiotherapy. In order to be able to definitively treat these patients, we assessed whether we could achieve a boost plan that would mimic our brachytherapy plans using external beam radiotherapy. Methods: High dose rate brachytherapy plans of 20 patients with stage IIB cervical cancer treated with definitive chemoradiotherapy were included in this study. Patients had undergone CT simulations with tandem and ovoids in place. Point “A” dose was 600-700 cGy. We attempted to replicate the boost dose distribution from brachytherapy plans using intensity-modulated radiotherapy (IMRT, Varian Medical Systems, Palo Alto, CA), volumetric modulated arc therapy (VMAT, Rapid Arc, Varian Medical Systems, Palo Alto, CA), or TomoTherapy (Accuray, Inc., Sunnyvale, CA) with the brachytherapy 100% isodose line as our target. Target coverage, normal tissue dose, and brachytherapy point doses were compared with ANOVA. Two-sided p-values ≤ 0.05 were considered significant. Results: External beam plans had excellent PTV coverage, with no difference in mean PTV V95% among planning techniques (range 98 – 100%). External beam plans had lower bladder Dmax, small intestine Dmax, and vaginal mucosal point dose than brachytherapy plans, with no difference in bladder point dose, mean bladder dose, mean small intestine dose, or rectal dose. Femoral head dose, parametria point dose, and pelvic sidewall point dose were higher with external beam techniques than brachytherapy. Conclusions: External beam plans had comparable target coverage and potential for improved sparing of most normal tissues compared to tandem and ovoid brachytherapy.